Brain SPECT imaging in Sydenham's chorea - Barsottini,O.G.P. (2002)
The objective of the present study was to determine whether brain single-photon emission computed tomography (SPECT) imaging is capable of detecting perfusional abnormalities. Ten Sydenham's chorea (SC) patients, eight females and two males, 8 to 25 years of age (mean 13.4), with a clinical diagnosis of SC were submitted to brain SPECT imaging. We used HMPAO labeled with technetium-99m at a dose of 740 MBq. Six examinations revealed hyperperfusion of the basal ganglia, while the remaining four were normal. The six patients with abnormal results were females and their data were not correlated with severity of symptoms. Patients with abnormal brain SPECT had a more recent onset of symptoms (mean of 49 days) compared to those with normal SPECT (mean of 85 days) but this difference did not reach statistical significance. Brain SPECT can be a helpful method to determine abnormalities of the basal ganglia in SC patients but further studies on a larger number of patients are needed in order to detect the phase of the disease during which the examination is more sensitive.